The Korean Wave
IX, 243 p.
Keywords: The rise in popularity of South Korean entertainment and culture began and is promoted as an official policy of the Korean government to revive the country's economy. This study examines cultural production and consumption, glocalization, the West versus. Asia, global race consciousness, and changing views of masculinity and femininity.